Axiokebuita Pocklington & Fournier 1987 ... - Persson, Jenny; Pleijel, Fredrik (Zenodo, 2005)
Axiokebuita Pocklington & Fournier, 1987 (Figs. 1, 2) Axiokebuita Pocklington & Fournier, 1987: 108. Type species. Kebuita minuta Hartman, 1967, by original designation (Pocklington & Fournier: 108). Material examined. ANTARCTIC: holotype for Axiokebuita minuta (USNM 55553, incl. 1 slide with parapodium), South Orkney Islands, 61°26’– 61°24’S, 41°55’W, 593–598 m, coll. USNS Eltanin, 13 Apr 1964; 1 spm (USNM 56626), Scotia Sea, 62°25’S, 56°30’– 56°32’W, 300 m, coll. USNS Eltanin, 13 March 1964; 2 spms (USNM 56625, incl. 2 slides with parapodia; Hartman’s original description recorded a single spm from this locality, but the vial actually includes 2 spms), Antarctic Peninsula, 64°54’S, 68°21’– 68°18’W, 412 m, coll. USNS Eltanin, 21 Oct 1962; 1 paratype for Axiokebuita millsi (USNM 60574), Ross Sea, 73°59’S, 170°41’E – 73°58’E, 170°58’S, 608 m, coll. USNS Eltanin, 13 January 1968. NORWAY, TRONDHEIMSFJORD: 2 spms (used for DNA sequencing), Rødberg, 63°28.32’N, 10°00.02’E, 230–280 m, Lophelia reef, ... : Published as part of Persson, Jenny & Pleijel, Fredrik, 2005, On the phylogenetic relationships of Axiokebuita, Travisia and Scalibregmatidae (Polychaeta), pp. 1-14 in Zootaxa 998 on pages 7-9, DOI: 10.5281/zenodo.171399 ...